Effect of antioxidants on the stability and corrosiveness of palm biodiesel upon exposure of different metals - Fazal, M.A.; Jakeria, M.R.; Haseeb, A.S. Md. Abdul; Rubaiee, S. (Elsevier, 2017)
The properties of biodiesel get aggravated when metals are exposed into it. The present study aims to investigate the effect of antioxidants on the fuel properties of palm biodiesel upon exposure to copper and mild steel. The used antioxidants include pyrogallol (PY) and butylated hydro-oxy toluene (BHT). Static immersion tests of metal coupons in palm biodiesel in the absence and presence (500 ppm) of antioxidants were conducted at room temperature (25˚C-27 °C) for 60 days. The investigated fuel properties include induction period, density, viscosity, acid number and calorific values. Results showed that pyrogallol was more effective to suppress the degradation of metal surface, fuel composition and fuel properties.